German version of the Hypogonadism Impact of Symptoms Questionnaire: Psychometric properties and association with testosterone levels. (21st January 2022) - Schmidt, Martina Kathrin; Rohayem, Julia; Zitzmann, Michael; Gelhorn, Heather; Schneider, Gudrun
Summary: In German, the 'Aging Males' Symptom Scale (AMS)' is available for the assessment of symptoms of hypogonadism in men of advanced age. An English questionnaire named 'Hypogonadism Impact of Symptoms' (HIS‐Q), applicable also in young males has recently been developed in the United States. We intended to: (1) evaluate the psychometric properties of the German translation of the short form of the HIS‐Q (HIS‐Q‐SF‐D); (2) explore the association of individual patient scores with their respective serum testosterone levels. The HIS‐Q‐SF‐D was completed by 174 men attending an Andrology outpatient clinic. Test–retest reliability was excellent, with high test–retest correlations (r = 0.883) and Cronbach`s Alpha of 0.948 for the total score. Convergent validity was supported by high Spearman`s correlation between the HIS‐Q‐SF‐D total score and the AMS total score (r = 0.817); also by the significant differences in the HIS‐Q‐SF‐domain scores between males with total testosterone levels above and below 12 nmol/l. Therefore, the HIS‐Q‐SF‐D shows good psychometric properties. As shown by the ROC‐analyses for testosterone above and below levels of 12 nmol/l, the HIS‐Q‐SF‐D cannot replace testosterone measurement for the establishment of the diagnosis of male hypogonadism.